Parental Use of Sun Protection for Their Children – Does Skin Colour Matter?. (1st June 2016) - Nag, S; Tan, M; Weinstein, M
Abstract: BACKGROUND: Excessive sun exposure during childhood years is a known risk factor for skin cancer. Fifty percent of lifetime UV exposure is acquired by age 19, highlighting the potential for prevention strategies in childhood. Existing guidelines from established pediatric, dermatology and cancer prevention societies are general and not specific to any skin phototype. OBJECTIVES: Our primary objective was to compare the frequency of adequate sun protection used by parents of children with different skin phototypes. Our secondary objective was to explore parental attitudes and beliefs on sun safety for their children. DESIGN/METHODS: Parents of children between the ages of 6 months to 6 years were systematically recruited. Parents received self-administered questionnaires containing 40-items that examine the amount of sun protection parents used on their children, as well as their attitudes and beliefs about sun safety. Parents were also requested to self-assess their child's Fitzpatrick Phototype (FP), and based on this response, they were divided into two groups: "lighter-skinned" (FP I-III) and "darker-skinned" (FP IV-VI). Guidelines from the Canadian Dermatology Association (CDA) on sun safety were used to quantify adequate sun protection. RESULTS: A total of 183 parents completed the questionnaires, and 150 eligible parents (the first 25 of each FP) were included in the study. Overall, only 17% of parents used adequate sun protection for their children. Parents of lighter-skinned children were significantly more likely to use adequate sun protection (OR=17.0). As their child got older, parents were also significantly less likely to use adequate sun protection for them (OR=0.64). A significantly larger portion of parents of lighter-skin children believe that sun exposure was harmful (OR=14.2) and perceived more value in sun protection (OR=14.2), whereas parents of darker-skin children were significantly more likely to believe that darker skin tones provided more sun protection (OR=4.1). CONCLUSION: Our study suggests that parental sun protection efforts were overall low, but especially in parents of darker-skinned children. The identified underlying attitudes and beliefs can aid in the design and delivery of sun protection interventions in the future, to ensure sun safety for all children, especially in a multiracial population.